Forced Vibration of a Nonlinear Stationary System with a Friction Clutch, Structural Friction Being Taken Into Consideration - Skup, Z. (Engineering Transactions, 1991)
The considerations are concerned with a nonlinear discrete stationary system containing a multiple-disc friction clutch, structural friction being taken into consideration. The system vibrates under harmonic excitation. Nonuniform distribution of pressure between the friction discs is taken into account. The influence of the dynamic system parameters upon the amplitude, vibration frequency and the phase shift angle is analysed. The equation of motion of the system is solved by the Van der Pol method.